“My teaching job is not what it used to be, and I'm looking for a way out:” A Mixed-Methods Examination of Teacher Stress Levels Following the COVID-19 Pandemic - Khalaifa, Mohamad; Hilton, Jason T. (Journal of Teaching and Learning, 2025)
Education following the COVID-19 pandemic is characterized by teacher stress, burnout, and turnover, leaving U.S. schools desperately short of teachers required to produce quality educational outcomes for students. This study aims to unpack current drivers of teacher stress and to provide options for educators looking to support K-12 teachers. A mixed-methods approach was utilized in surveying K-12 teachers (N = 295) within multiple school districts throughout Western Pennsylvania. Results show that time management, student discipline, and increased workloads are primary drivers of teacher stress, with insights that changes in student motivation, the volume of teachers’ work, lack of administrative support, and teachers’ struggles with mental health, led to increased stress. Suggestions for ways to support teachers experiencing stress are presented.